Relaxing Hukou: Increased labor mobility and China's economic geography - Maarten Bosker; Steven Brakman; Harry Garretsen; Marc Schramm (Center for Economic Studies and ifo Institute (CESifo), 2010)
China's Hukou system poses severe restrictions on labor mobility. This paper assesses the consequences of relaxing these restrictions for China's internal economic geography. We base our analysis on a new economic geography model. First, we obtain estimates of the important model parameters on the basis of information on 264 of China's prefecture cities over the period 1999-2005. Second, and by using our estimation results as input, we simulate various long-run scenarios of China's internal economic geography that differ in their degree of interregional labor mobility. We find that increased labor mobility will lead to more pronounced core-periphery outcomes. Interestingly, these agglomerations are not necessarily along the coastal regions. Given the increased importance of China's internal market, firms agglomerate in the populous heartland of China. China's internal demand will be the most important determinant of its future economic geography.
Keywords: O18; R11; R12; 330; Empirical and Theoretical Methods; Regionale Arbeitsmobilität; Kern-Peripherie-Beziehung; Wohnungspolitik; Ballungsraum; China